Decision to delivery interval targets: an overview of the challenges. (18th April 2012) - Stephen, GL; Croft, R; MacLennan, K; Gillham, JC
Abstract : Background: It is well established that prolonged decision to delivery intervals (DDI) can result in poor outcomes for both mother and infant in emergency caesarean section.1 As such, national guidance is provided on DDI targets which is 30 and 75 minutes for category 1 and 2 caesarean sections respectively. Adherence to DDI targets is integral to optimal maternity service and failure to do so can give grounds for litigation when outcomes are poor. Method: Data was retrospectively collected from emergency caesarean sections where the DDI target was breached from January to June 2011. Information gathered included category of caesarean section, whether the procedure was performed "out of hours", time from decision to theatre, time taken to commence anaesthetic, knife to skin to delivery, neonatal and maternal outcome and reason for delay in meeting target. Trends were then compared with previous audits Results: 276 caesarean sections were performed (125 grade 1, 151 grade 2). DDI targets were breached 28% of grade 1 and 23% of grade 2. Reasons given included delay getting into theatre, anaesthetic delays and patient factor and apparent communication errors. Discussion: These findings re-iterate the importance of transferring the patient into theatre within 10 minutes in emergency situation to enable meeting DDI targets. Communication between team members is paramount to ensure all members of the time are aware of the timescale to work to. As our unit expands due to local reconfiguration of maternity services the need for a second theatre is likely to increase.